Wet chemical routes to the assembly of organic monolayers on silicon surfaces via the formation of Si-C bonds: Surface preparation, passivation and functionalization - Ciampi, Simone; Harper, J.; Gooding, J. (RSC Publishing, 2010)
Organic functionalization of non-oxidized silicon surfaces, while allowing for robust chemical passivation of the inorganic substrate, is intended and expected to broaden the chemical, physical and electronic properties of the currently most relevant technological material. Numerous protocols are now available for the preparation of Si-C, Si-O and Si-N bound layers. In particular, the covalent attachment of 1-alkenes and 1-alkynes onto hydride-terminated Si(100) and Si(111) has seen a wealth of research activity starting from the pioneering work of Linford and Chidsey (Alkyl monolayers covalently bonded to silicon surfaces, J. Am. Chem. Soc., 1993, 115(26), 12631-12632). This critical review aims to bring together the available wet-chemical routes toward the formation of silicon-organic monolayers under ambient conditions. Particular emphasis is placed on discussing the reasons behind the need for novel chemical approaches that are straightforward, modular and of wide scope so as to allow the application of silicon electrodes in aqueous electrolytes. A general introduction to biomolecular recognition events at functionalized silicon surfaces is also presented (281 references). © The Royal Society of Chemistry 2010.